Augmented peripheral nerve regeneration through elastic nerve guidance conduits prepared using a porous PLCL membrane with a 3D printed collagen hydrogel - Yoo, Jin; Park, Ji Hun; Kwon, Young Woo; Chung, Justin J.; Choi, In Cheul; Nam, Jae Joon; Lee, Hyun Su; Jeon, Eun Young; Lee, Kangwon; Kim, Soo Hyun; Jung, Youngmee; Park, Jong Woong (ROYAL SOC CHEMISTRY, 2020)
Peripheral nerve injury results in significant sensory and motor functional deficits. Although direct neurorrhaphy in the early phase may reduce its devastating effects, direct end-to-end neurorrhaphy is sometimes impossible owing to a defect at the injured site of the nerve. Autogenous nerve graft is a primary consideration for peripheral nerve defects; however, significant morbidity of the donor site is inevitable. Recently, the treatment using engineered synthetic nerve conduits has been regarded as a promising strategy to promote the regeneration of peripheral nerve defects. In this study, we developed longitudinally oriented collagen hydrogel-grafted elastic nerve guidance conduits (NGC) to reconstruct sciatic nerve defects. An elastic NGC was prepared by using poly(lactide-co-caprolactone) (PLCL), and electrospun PLCL was adopted to fabricate nanoporous structures with appropriate permeability for nerve regeneration. Oriented collagen hydrogels were prepared by the 3D printing method to achieve a microscale hydrogel pattern. Based on sciatic nerve injury models in rats, we confirmed the beneficial effects of the NGC with 3D printed collagen hydrogel on axonal regeneration and remyelination along with superior functional recovery in comparison with the NGC filled with the bulk collagen hydrogel. It is believed that the aligned collagen hydrogels provide a preferable environment for nerve regeneration, functioning as an oriented guidance path. In conclusion, the PLCL nerve guide conduit containing a 3D printed aligned collagen hydrogel can be useful for peripheral nerve regeneration.
Keywords: GROWTH-FACTOR; SCAFFOLDS; CHITOSAN; MATRICES; BEHAVIOR; MODEL